2021
DOI: 10.7717/peerj.10991
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing student choice of a degree in physiotherapy: a population-based study in Catalonia (Spain)

Abstract: Background In other healthcare professions, there has been extensive research into students’ motivation, but studies aiming to determine what leads individuals to choose a degree in physiotherapy are scarce. This research study had three main objectives: to obtain a sociodemographic profile of first-year physiotherapy students in Catalonia; to determine the factors that lead individuals to choose a degree in physiotherapy; and to determine potential differences, according to gender and country o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…On the other hand, men reported being more motivated by good salary prospects and job prestige. In the same vein, a previous study conducted in Catalonia (Spain) also found male physiotherapy students to be more interested in employability and income prospects [37]. Beyond the COVID-19 pandemic scenario, in a previous study female nursing students scored higher in values focused on social or affective relationships, while male nursing students scored higher in stereotypical masculine values such as dominance and success [43].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…On the other hand, men reported being more motivated by good salary prospects and job prestige. In the same vein, a previous study conducted in Catalonia (Spain) also found male physiotherapy students to be more interested in employability and income prospects [37]. Beyond the COVID-19 pandemic scenario, in a previous study female nursing students scored higher in values focused on social or affective relationships, while male nursing students scored higher in stereotypical masculine values such as dominance and success [43].…”
Section: Discussionmentioning
confidence: 78%
“…Healthcare students usually pursue their future profession due to intrinsic factors such as personal motivations (e.g., interest in the sciences) and humanitarian factors (e.g., serve the community, help and care for others), sociodemographic factors (e.g. gender, socioeconomic status), extrinsic factors (e.g., employability, financial security, expectations of salary, diversity of job opportunities) and interpersonal factors (e.g., family, friends, prestige, social influence and recognition [34,37]. According to a previous study, these mediators were altered during the COVID-19 pandemic, not only in the enrolled undergraduate students [14] but also in future students considering studying a health-related degree, because the main interests were focused on the desire to help others, reinforce citizenship values, and improve the country's situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teaching is mostly associated with patient assessment and treatment Absolutely Agree Agree opportunities. (17) The performance is based on clinical trainings and patient exposure during study years, which is predictor of license exams in different countries. (18) The overall satisfaction of students was good regarding knowledge, future beliefs, patient exposure and learnings in their institutes.…”
Section: Good Theoretical Backgroundmentioning
confidence: 99%
“…Os estudos de Akodu et al e Fuente-Vidal et al investigaram e analisaram sobre a percepção dos alunos da graduação de fisioterapia de anos finais sobre o curso e o seu campo de atuação, bem como as perspectivas no mercado de trabalho, de maneira geral (Akodu et al, 2018;Fuente-vidal et al, 2021). Os resultados desses estudos sugerem que a fisioterapia está associada a um alto nível de prestígio ocupacional entre os participantes, com expectativa de bons salários, empregabilidade e múltiplas oportunidades de trabalho, além de o desejo de ajudar e cuidar dos outros ser o fator predominante na escolha de cursar a graduação (Akodu et al, 2018;Fuente-vidal et al, 2021).…”
Section: Introductionunclassified